Development of Real-Time PCR Assay to Specifically Detect 22 Bifidobacterium Species and Subspecies Using Comparative Genomics - Kim, Hyeon-Be; Kim, Eiseul; Yang, Seung-Min; Lee, Shinyoung; Kim, Mi-Ju; Kim, Hae-Yeong (Frontiers in Microbiology, 2020)
Bifidobacterium species are used as probiotics to provide beneficial effects to humans. These effects are specific to some species or subspecies of Bifidobacterium. However, some Bifidobacterium species or subspecies are not distinguished because similarity of 16S rRNA and housekeeping gene sequences within Bifidobacterium species is very high. In this study, we developed a real-time polymerase chain reaction (PCR) assay to rapidly and accurately detect 22 Bifidobacterium species by selecting genetic markers using comparative genomic analysis. A total of 210 Bifidobacterium genome sequences were compared to select species- or subspecies-specific genetic markers. A phylogenetic tree based on pan-genomes generated clusters according to Bifidobacterium species or subspecies except that two strains were not grouped with their subspecies. Based on pan-genomes constructed, species- or subspecies-specific genetic markers were selected. The specificity of these markers was confirmed by aligning these genes against 210 genome sequences. Real-time PCR could detect 22 Bifidobacterium specifically. We constructed the criterion for quantification by standard curves. To further test the developed assay for commercial food products, we monitored 26 probiotic products and 7 dairy products. Real-time PCR results and labeling data were then compared. Most of these products (21/33, 63.6%) were consistent with their label claims. Some products labeled at species level only can be detected up to subspecies level through our developed assay.